(untitled) (Revista Puertorriqueña de Psicologia, 2016)
This study was designed to determine the relationship of Locus of Control to undecided college students’ satisfaction with a self - administered vocational counseling treatment and an interview - oriented counseling treatment. It was predicted that internally oriented students would be more satisfied with the self - administered treatment, while externally oriented students would be more satisfied with a counselor - mediated treatment. A sample of 160 students was given the Rotter Internal-External Scale, alternately the Self-Directed Search (SDS) or Vocational Preference Inventory (VPI), and a previously used satisfaction questionnaire. No significant relationship was found between Locus of Control and students’ level of satisfaction with either treatment. These findings suggest that Locus of Control is not a discriminating variable mediating satisfaction with a self - administered or an interview-oriented vocational counseling treatment.